(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
In today’s world, the problem of rational use of resources and preserving the ability of the environment to maintain a sustainable ecosystem is increasing. At the same time, the amount of waste produced by businesses is increasing, leading to environmental degradation and resource scarcity. The concept of the circular economy is an alternative approach to doing business that can significantly reduce waste, increase resource efficiency and reduce environmental impact.